PENGARUH MEDIA KOMIK TERHADAP PENINGKATAN MOTIVASI DAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN IPA - SUSIANI SUSIANI (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2022)
Motivation is often a problem faced in the world of education. There are several things that cause a lack of student motivation, one of which is the presentation of learning materials that are less attractive and tend to be monotonous. Learning that is not interesting and monotonous will result in students being reluctant to pay attention, and preferring to play or do other activities while learning is in progress. If this continues, it will be able to affect student achievement. In this study, the researcher wanted to know the effect of comics media in increasing students' motivation and learning achievement using the descriptive method of Interrelationship Studies. With data collection techniques by observation and objective tests. At the time of the study, it was found that there was a significant effect on increasing students' motivation and learning achievement after using comics media. Students' motivation and learning participation increased by 39.39% in the first cycle, while in the second cycle there was an increase of 45.45%. This increase in motivation is in line with the increase in student achievement, namely 41.41% on the first daily test and 46.46% on the second daily test. ABSTRAKMotivasi sering menjadi masalah yang dihadapi dalam dunia pendidikan. Ada beberapa hal yang menjadi penyebab kurangnya motivasi belajar siswa, salah satunya adalah penyajian materi pembelajaran yang kurang menarik dan cenderung monoton. Pembelajaran yang tidak menarik dan monoton akan mengakibatkan siswa menjadi enggan untuk memperatikan, dan lebih suka bermain atau mengerjakan kegiatan lain saat pembelajaran sedang berlangsung. Jika hal ini terus berlanjut akan dapat berpengaru terhadap prestasi belajar siswa. Dalam penelitian ini, peneliti ingin mengetahui pengaruh media komik dalam meningkatkan motivasi dan prestasi belajar siswa menggunakan metode deskriptif Studi Hubungan (Interrelationship Studies). Dengan teknik pengumpulan data secara observasi dan tes objektif. Pada saat penelitian ditemukan adanya pengaruh yang cukup signifikan terhadap peningkatan motivasi dan prestasi belajar siswa setelah menggnakan media komik. Motivasi dan partisivasi belajar siswa meningkat sebesar 39,39 % pada siklus satu, sedangkan pada siklus dua ada peningkatan 45,45 %. Peningkatan motivasi ini sejalan dengan peningkatan prestasi hasil belajar siswa yang dicapai, yaitu 41,41% pada ulangan haruan pertama dan 46,46 % pada ulangan harian kedua.